2019
DOI: 10.1177/2471549219826365
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Method for Preclinical Durability Evaluation of Linked Semiconstrained Total Elbow Replacement Prostheses

Abstract: Total elbow replacement (TER) is a clinically successful procedure yet isolated, gross mechanical complications associated with implant durability persist. The objectives of this study were to (1) develop a clinically relevant in vitro methodology to replicate the reported damage modes and (2) demonstrate durability improvements of a next-generation linked, semiconstrained design. Two TER prostheses were tested on a biaxial test frame at 1.4 Hz in 37 AE 3 deionized water through 0 to 130 flexion/extension at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…The JRF angle with respect to the humerus was consistent with the pattern described by Kincaid and An . A medial‐lateral force was coupled with the pure VV moment, based on visual interpretation of how VV loads were applied by Varadarajan et al…”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…The JRF angle with respect to the humerus was consistent with the pattern described by Kincaid and An . A medial‐lateral force was coupled with the pure VV moment, based on visual interpretation of how VV loads were applied by Varadarajan et al…”
Section: Methodssupporting
confidence: 78%
“…Their study did not prescribe an exact magnitude for applied loading, but a general pattern for joint reaction force (JRF) and JRF angle, both as a function of weight‐in‐hand (WIH) and flexion angle. Results presented by Varadarajan et al using a similar loading pattern indicated that the 200 K cycle run‐out load for this implant occurred with a maximum joint reaction force (JRF) of 1,511 N (10.2 kg WIH) and a sinusoidal ±4.9 Nm varus‐valgus (VV) moment, during cyclical flexion–extension from 0° to 130°. Higher loading than this induced component failure (including snap‐pin failure) before 200 K cycles.…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations